The impact of disease severity measures on survival in U.S. veterans with rheumatoid arthritis-associated interstitial lung disease. (4th April 2022) - Brooks, Rebecca; Baker, Joshua F; Yang, Yangyuna; Roul, Punyasha; Kerr, Gail S; Reimold, Andreas M; Kunkel, Gary; Wysham, Katherine D; Singh, Namrata; Lazaro, Deana; Monach, Paul A; Poole, Jill A; et al.
Abstract: Objectives: To determine whether RA and interstitial lung disease (ILD) severity measures are associated with survival in patients with RA-ILD. Methods: We studied US veterans with RA-ILD participating in a multicentre, prospective RA cohort study. RA disease activity (28-joint DAS [DAS28-ESR]) and functional status (multidimensional HAQ [MDHAQ]) were collected longitudinally while pulmonary function tests (forced vital capacity [FVC], diffusing capacity for carbon monoxide) were obtained from medical records. Vital status and cause of death were determined from the National Death Index and administrative data. Predictors of death were assessed using multivariable Cox regression models adjusting for age, sex, smoking status, ILD duration, comorbidity burden and medications. Results: We followed 227 RA-ILD participants (93% male and mean age of 69 years) over 1073 person-years. Median survival after RA-ILD diagnosis was 8.5 years. Respiratory diseases (28%) were the leading cause of death, with ILD accounting for 58% of respiratory deaths. Time-varying DAS28-ESR (adjusted hazard ratio [aHR] 1.21; 95% CI: 1.03, 1.41) and MDHAQ (aHR 1.85; 95% CI: 1.29, 2.65) were separately associated with mortality independent of FVC and other confounders. Modelled together, the presence of either uncontrolled disease activity (moderate/high DAS28-ESR) or FVC impairment (<80% predicted) was significantly associated with mortality risk. Those with a combination of moderate/high disease activity and FVC <80% predicted had the highest risk of death (aHR 4.43; 95% CI: 1.70, 11.55). Conclusion: Both RA and ILD disease severity measures are independent predictors of survival in RA-ILD. These findings demonstrate the prognostic value of monitoring the systemic features of RA-ILD.